Generation and characterization of plasma jet and its effect on seeds - Thakur, Bablu Kant; Shah, Arun Kumar; Sah, Ram Lal; Silpakar, Reeta; Shrestha, Rajendra; Mishra, Lekha Nath (BIBECHANA, 2026)
These days, atmospheric pressure plasma jet technology is regarded as one of the most practical instruments in a number of domains, such as agriculture, plasma medicine, and surface modification. A quartz glass tube with an internal diameter of 3 mm and an exterior diameter of 5 mm is used to create the plasma jet. The electrodes are 8 cm apart and have a width of 1.0 cm. They are composed of aluminum foil which wraps the glass tubes. As a working gas, argon is utilized. The power supply has a frequency of 27 kHz and a voltage of 20 kV. Electron density and electron temperature have been established in order to describe plasma. The stark broadening method and power balance are used to determine the electron density. The line intensity ratio method is used to determine the electron temperature. It is revealed that applied voltage and gas flow rate affect both electron density and temperature.